Retinopathy of prematurity: prevalence, screening and treatment - Alnahdi, Ahmed Thabit; Althemairi, Alaa Ahmed; Al-Qahtani, Khalid Mohammed; Alharbi, Abdulmohsen M.; Alenezi, Ahmad; Alkathery, Faisal Sulaiman; Almahdi, Hussein Ahmed; Al Majbar, Yahya Ayed; Asiri, Hamad Mohammed; Alajmi, Mohammad Rashed; Alaskar, Abdulaziz Abdullah (International Journal Of Community Medicine And Public Health, 2023)
Retinopathy of prematurity (ROP) is a serious ocular condition arising from improper blood vessel development in the retina, predominantly affecting infants born prematurely or with a birth weight under 1500 g. A global estimate from 2010 indicated that approximately 184,700 infants developed ROP, with around 50,000 progressing to severe stages, yet only 42% received treatment. This article undertakes a thorough review, commencing on 07th November 2023, leveraging databases like Pubmed and Cochrane to synthesize current knowledge and emerging trends in ROP prevalence, screening methodologies, and treatment options. Screening involves repeated eye exams and innovative tools to identify high-risk infants early on. Treatment approaches, encompassing cryotherapy, laser therapy, and anti-VEGF (vascular endothelial growth factor) medications, are tailored to the severity of ROP. Rigorous follow-up assessments are pivotal for tracking progress and ensuring the welfare of infants undergoing ROP interventions. This comprehensive exploration seeks to enhance awareness and understanding of ROP’s global prevalence, screening protocols, and evolving treatments, ultimately contributing to informed decision-making and the advancement of best practices in the early identification and management of ROP among premature infants.